2017
DOI: 10.1111/jwas.12429
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Feedstuff Digestibility for Snook, Centropomus undecimalis, Juveniles

Abstract: The degree of hydrolysis (DH) of the ingredients was evaluated for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
7
1
1
Order By: Relevance
“…Six diets were prepared by combining a test ingredient (30%) with the reference diet (70%), and acid‐insoluble ash (AIA) was used as a marker (Table 2; Lemus et al. 2018; Parra‐Flores et al. 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six diets were prepared by combining a test ingredient (30%) with the reference diet (70%), and acid‐insoluble ash (AIA) was used as a marker (Table 2; Lemus et al. 2018; Parra‐Flores et al. 2020).…”
Section: Methodsmentioning
confidence: 99%
“…2014; Lemus et al. 2018). Therefore, the comprehensive evaluation of potential ingredient substitutes for FM is imperative to foster the sustainable development of aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…It is sure enough that soybean is the second protein ingredient studied most by in-vitro digestion, given its global recognition as high protein feed material. By using an in-vitro digestion model, several studies have evaluated the effect of inhibitors and phytic acid on the digestibility of soybean to be utilized as a fish meal substitute [86][87][88]. Substitution of fish meal with soybean formulated as a fish feed had been studied on several different levels ranging from none to total replacement [83,84].…”
Section: Current In-vitro Digestion Studies On Fishmentioning
confidence: 99%
“… nd. 37 15 11 protein ingredients DH, FAA APD Centropomus undecimalis Two stage pH stat [ 87 ] 8 - 25 60 10 protein ingredients DH, invivo Acipenser baeri One step intestine stage, [ 168 ] 3.4&7.8 256 & 1460 28 90 acid Poultry by product on several different grade Pepsin assay FAA APD Lates calcarifer Two stage membrane reactor, with commercial pepsin and fish crude intestinal extract [ 169 ] 9 2.5 25 90 4 microalgae SDS page, FAA Senegalese sole One stage intestinal digestion [ 170 ] 2 & 7 nd 37 120 & 120 Three commercial diet In vivo assessment Residual protein Minerals (P, Fe, Zn) P.mesopotamicus Two step digestion with final product dialysis separation. Added bile extract [ 16 ] 3.5 & 8 - - 15&45 16 protein ingredients DH, FAA Amphilophus trimaculatus Intestinal...…”
Section: Application Of In-vitro Digestion Model I...mentioning
confidence: 99%
“…Regarding the nutritional requirements, previous reports have revealed that common snook has a protein requirement in the diet of 500 g kg −1 (Concha‐Frías et al, 2018; Gracia‐López et al, 2003; Tucker, 1987). Additionally, in a recent study, Lemus et al (2018) proposed a selection of marine and terrestrial ingredients as an alternative source to fishmeal protein for common snook feeds. To date, no studies have been performed on the ability of common snooks to utilize lipids as energy sources.…”
Section: Introductionmentioning
confidence: 99%